2017
DOI: 10.1080/08927014.2017.1336619
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the quorum sensing regulated pathogenic traits of the biofilm-forming fish pathogenAeromonas hydrophilaby tannic acid, a potent quorum quencher

Abstract: The quorum sensing (QS) phenomenon regulates a myriad of pathogenic traits in the biofilm forming fish pathogen, Aeromonas hydrophila. Blocking the QS mechanism of A. hydrophila is a novel strategy to prevent disease in fish. This study evaluated the effect of tannic acid, a QS inhibitor, on A. hydrophila-associated QS regulated phenomena. A streaking assay with Chromobacterium violaceum (CVO26) reported the presence of N-acyl homoserine lactone (AHL) in A. hydrophila, which was confirmed by HPLC and GC-MS ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…This information might be useful to design QS inhibitors. The same occurs with tannic acid, a potent quorum quencher that regulates the biofilm formation of A. hydrophila [265].…”
Section: Quorum Sensingmentioning
confidence: 90%
See 1 more Smart Citation
“…This information might be useful to design QS inhibitors. The same occurs with tannic acid, a potent quorum quencher that regulates the biofilm formation of A. hydrophila [265].…”
Section: Quorum Sensingmentioning
confidence: 90%
“…The "signal" molecule in Gram-negative bacteria is N-acyl homoserine-lactone (AHL) and in Aeromonas, the AHL is able to modulate the host immune response [19,186,259]. Several studies have shown the importance of AHLs in regulating a range of biological functions such as biofilm formation, antibiotic production, and warming motility and the different QS systems harbor differences in their influences [260][261][262][263][264][265][266]. Chan et al [260] found in the whole genome of the strain A. veronii 159 sequences of QS-related genes, providing a model for exploring it roles in virulence and as a potential target for Aeromonas treatment.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…This study also confirmed that A. veronii isolated from the intestinal tract of fish was different from that isolated from the aquatic environment. Aerolysin is the main virulent factor in Aeromonas, contributing to bacterial pathogenesis [33,34]. However, in the 1990s, the aerolysin gene had not been detected in any A. veronii isolates [35].…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric also has been reported able to inhibit virulence genes expression on P. aeruginosa [18]. Tannic acid-treated A. hydrophila showed a considerable reduction in violacein production, blood hemolysis activity, the pattern of swarming motility and biofilm formation [16]. Quorum sensing have been known regulates expression of various virulence factor genes from pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%